Description of Students' Knowledge about Human Papilloma Virus Immunization as a Cervical Cancer Prevention Strategy - Ksatria Ningtyas, Anak Agung Istri Wulan; Budiani, Ni Nyoman; Eka Utarini, Gusti Ayu (Jurnal Midwifery, 2026)
Introduction One of the cancers that often occur in women is cervical cancer. In 2020, there were 234.51 deaths due to cervical cancer and 36,633 new cases (17.2%) of the disease, according to Globocan data. Premarital sexual relations in adolescents can cause cervical cancer; prevention can be done through human papillomavirus (HPV) immunization. The purpose of this study was to determine the overview of female students' knowledge about human papillomavirus immunization as a cervical cancer prevention strategy at State Senior High School 1 Amlapura. Method This type of research is descriptive. This study was conducted in April 2025 with 156 respondents selected through simple random sampling. Data collection used a questionnaire containing 15 questions about knowledge about HPV immunization. Data analysis used univariate analysis with the presentation of frequency distribution data. Result The results showed that a small  respondents, namely 20 respondents, had good knowledge. Conclusion It is hoped that female students will be more active in seeking information about HPV immunization and that there will be support from families, schools, and health facilities in the school environment to provide counseling regarding the importance of preventing cervical cancer